The competitive behaviour of rural households in agriculture: A case study ÷Tara Haðtegului - Lorena Florentina Chiţea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The goal of this paper is represented by the analysis of the competitive behaviour at rural household level in ðTara Haðtegului, according to the economic size of the agricultural activities performed. If we extrapolate the mechanism from firm level to agricultural household level, competitiveness operates as a selection mechanism (only certain agricultural household farms survive on the market, which obtain quality products and have more efficient production processes); this also acts as a stimulation mechanism (in order to continue to exist on the market, the rural household farms must improve their technology and production organization). Competitiveness increase in agriculture first means a major change with regard to the agricultural behaviour, both at rural household level and at the level of (local and governmental) authorities. But the greatest obstacle to the change of farmers' behaviour presupposes a fundamental transformation of their values and lifestyle, which is quite difficult.
Keywords: 330; competitiveness; agricultural household; economic size